Prevalence of Anaemia among Patients attending Central Laboratory at a Tertiary Care Centre in Nepal (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Anaemia is a very common problem in developing country like Nepal among children’s and young females. It is necessary to detect haemoglobin at early stage to know about anaemia. Anaemia in female causes dizziness and loss of concentration, which may lead to fall down and cause severe injury. In pregnant woman anaemia leads to developmental delay in children. In anaemic pregnant females, loss of blood during delivery can cause complications and even death of mother and foetus. In children iron deficiency anaemia may cause loss of concentration, developmental delay and delay in maturity of brain.MATERIALS AND METHODS: This prospective, cross-sectional study was carried out at Rapti Academy of Health Sciences from 1st March 2019 to 1st April 2019. A total of 1000 samples which came in central laboratory on regular basis were taken and Mindray 5 part hematology analyzer was used to evaluate the samples. In samples with low haemoglobin count, peripheral smear examination was done to determine the type of anaemia.RESULTS: Patient blood samples were taken irrespective of age and sex. Out of the total 1000 cases from various Outpatient departments of Rapti Academy of Health Sciences, 240 (24%) patients were anaemic.CONCLUSIONS: Anaemia is a major problem worldwide and the most common anaemia is microcytic hypochromic anaemia, especially iron deficiency anaemia followed by megaloblatic anaemia and hemolytic anaemia. Thus, it is necessary to do haemoglobin count and stool examination of woman in hilly regions on a regular basis, which will be helpful to avoid further anaemia related complications.